PENEGAKAN HUKUM TERHADAP PELANGGARAN RIGHT OF WAY OLEH PERUSAHAAN PROPERTI DI KOTA SURABAYA - Sholehuddin, Muhammad (Fakultas Hukum Universitas Narotama, 2025)
This study aims to analyze the legal basis for the violation of the Right of Way of the Surabaya city government and the consequences for housing built by property companies in the city of Surabaya. This study uses a normative legal research type with a statute approach. Primary sources of legal materials include laws and regulations that regulate the right of way, namely East Java Provincial Regulation Number 10 of 2023, Surabaya City Regional Regulation Number 33 of 2019 concerning Road Implementation, Government Regulation Number 21 of 2021 and so on. Meanwhile, secondary sources of legal materials include legal literature, books, journals, articles, and legal studies that discuss the implementation of the right of way, dispute resolution, and corporate legal responsibilities in property development or the like. The data collection technique is carried out through document studies, namely reviewing relevant legal documents and identifying how they are applied in violation cases in the city of Surabaya. Then it is systematically analyzed to get relevant and in-depth conclusions. The results of his research explain that the Surabaya City government has a legal basis to enforce the law against violations of the Right of Way by property companies through several regulations as explained in the discussion. Violations of the Right of Way by property companies in Surabaya can have serious legal consequences, both for the company and the housing they build. Keywords: Law Enforcement, Right of Way, Property Companies